Analysis of Smart Infrastructure Implementation in Facilities and Infrastructure of Supporting Hospital for Nusantara Capital City: Bahasa Indonesia - Rahmad; Oryza Lhara Sari (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
As part of the 100 Smart Cities program and a buffer for the Nusantara Capital City (IKN), Balikpapan City is facing a population growth that has the potential to increase. This growth affects the quality of health services at Hospital X in Balikpapan City, where physical and digital infrastructure needs to be improved to accommodate the needs of patients and visitors. Infrastructure challenges include improving waste management facilities and infrastructure that are still inadequate in line with the increase in patients, as well as the lack of facilities for people with disabilities throughout the hospital area. Therefore, the purpose of this study is to analyze the application of the smart infrastructure concept based on the priority level of variables between mobility, energy management, networks and telecommunications, waste and waste management, and health variables, so that it is expected to provide quality from the existing physical and digital infrastructure to staff workers, patients, and hospital visitors. The results of the analysis using the Analytical Hierarchy Process method obtained a priority scale based on the weight value obtained is Mobility (0.252) with the implementation of a smart parking system (0.208), Energy Management (0.208) with the implementation of smart renewable energy (0.354), Waste and Waste Management (0.197) with the implementation of smart waste bins (0.353), Network and Telecommunication (0.195) with the implementation of automatic attendance using fingerprints (0.369), and Health (0.149) with the implementation of medical sensors to monitor chronic disease patients (0.237).